PENGGUNAAN INFORMASI DEBITOR DARI SISTEM LAYANAN INFORMASI KEUANGAN OTORITAS JASA KEUANGAN (SLIK OJK) SEBAGAI ALAT BUKTI PERMOHONAN PKPU - Simanjuntak, Jimmy (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Suspension of debt payment (PKPU) is an Indonesian Bankruptcy Law instrument to resolve disputes over receivables through reconciliation between debtors and creditors, so that debtors can continue their business. Parties that can submit a PKPU application are creditors and debtors themselves. If the creditor submits an application for PKPU against the debtor, then the creditor is obliged to simply prove the fulfillment of Article 2 paragraph (1) of the KPKPU Law, where the debtor has more than one creditor and there is a debt that is due and collectible. This study aims to analyze the use of debtor information from SLIK OJK which is used as valid evidence, to fulfill the requirements of Article 8 paragraph (4) jo. Article 2 paragraph (1) of the KPKPU Law in the PKPU application submitted by creditors. In the event that the creditor is a business entity in the banking sector, in the case of a commercial bank, it has the right to access debtor information from the OJK SLIK as stipulated in Article 2 paragraph (1) jo. Article 14 paragraph (2) POJK 18/POJK.03/2017, the creditor can submit debtor information from SLIK OJK as evidence to prove the existence of other creditors who have receivables from the same debtor. The validity of using debtor information from SLIK OJK as evidence is confirmed by Decision No. 92/Pdt.Sus-PKPU/2023/PN Niaga.Jkt.Pst. however, the use of data from the OJK SLIK in submitting PKPU applications must be carried out with caution and limited to the existence of debtors’ debts contained in the OJK SLIK data.